Pengaruh Islamic Market Orientation dan Inovasi Produk terhadap Kinerja Pemasaran UMKM Muslim di Panyabungan - Amalia Rahman Nasution; Annio Indah Lestari; Rahmat Daim Harahap (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
AbstractThis study aims to determine the effect of Islamic market orientation and product innovation on marketing performance. The sample used was 70 people obtained using the Slovin formula. Collecting data through a questionnaire directly to respondents namely muslim MSMEs in Panyabungan using a Likert scale. The data analysis technique used in multiple regression analysis with SPSS. The results ot the analysis show that Islamic market orientation has a positive and significant effect on marketing performance and product innovation has a positive and significant effect on marketing performance.Key Words: Islamic market orientation, product innovation, marketing performance